2016
DOI: 10.15850/amj.v3n2.467
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Pulsatilla chinensis towards Staphylococcus aureus, Shigella dysenteriae, and Salmonella typhi

Abstract: Background: Pulsatilla (P.) chinensis is a kind of traditional Chinese medicine (TCM) that has antibacterial effect. It is used to treat diarrhea, dysentery, and other diseases. The P. chinensis is composed of some potent antibacterial substances including protoanemonin, saponin, oleanolic acid. The study aimed to determine the antibacterial effect of P. chinensis towards staphlococcus aureus, Shigella dysenteriae, and Salmonella typhi. Methods:This was an experimental descriptive study that was conducted in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The broth microdilution method [ 29 ] was used to screen for antibacterial activity of A. pilosa Ledeb, S. glabra Roxb, A. chinensis Bunge, and I. domestica (L.) Goldblatt and Mabb against L. monocytogenes, E. coli, and S. enteritidis . The selection of plants was based on longstanding traditional claims [ 12 ] and current knowledge [ 20 , 33 , 34 , 35 ] of their antibacterial activities. A review of the literature highlighted that there is a lack of research investigating the antibacterial properties of the aqueous extracts of A. pilosa Ledeb, S. glabra Roxb, A. chinensis Bunge, and I. domestica (L.) Goldblatt and Mabb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broth microdilution method [ 29 ] was used to screen for antibacterial activity of A. pilosa Ledeb, S. glabra Roxb, A. chinensis Bunge, and I. domestica (L.) Goldblatt and Mabb against L. monocytogenes, E. coli, and S. enteritidis . The selection of plants was based on longstanding traditional claims [ 12 ] and current knowledge [ 20 , 33 , 34 , 35 ] of their antibacterial activities. A review of the literature highlighted that there is a lack of research investigating the antibacterial properties of the aqueous extracts of A. pilosa Ledeb, S. glabra Roxb, A. chinensis Bunge, and I. domestica (L.) Goldblatt and Mabb.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extraction methods are inexpensive and the bioactive compounds are less toxic and therefore more suitable for use as a poultry feed supplement. Furthermore, the antibacterial activity of the aqueous extract of Anemone chinensis Bunge exhibited antibacterial activity against Staphylococcus aureus during disc diffusion, highlighting its antibacterial properties [20]. A. pilosa Ledeb, S. glabra Roxb, A. chinensis Bunge, and I. domestica (L.) Goldblatt and Mabb are listed in the Chinese Pharmacopoeia [21] and are used to treat infections in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our study, Cheng et al [19] reported tha that Escherichia coli was the commonest organism in mastitis cases, and Streptococcus uberis continued to be a prevalent pathogen closely followed by Staphylococcus aureus, Streptococcus dysgalactiae and Streptococcus agalactiae. Pulsatilla chinensis have inhibitory effects on Staphylococcus aureus, Streptococcus dysenteriae and Salmonella typhi [9]. Shafaghat [20] reported that Pulsatilla showed moderate inhibitory activity against some certain strains in Gram-positive and Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsatilla saponin B4 is the main active ingredient of Pulsatilla chinensis (Bunge) Rege and plays a therapeutic role in the case of mastitis as an anti-in ammatory, anti-bacterial, and immune regulating agent [7,8]. Recent studies showed that Pulsatilla chinensis has inhibitory effects on Staphylococcus aureus, Streptococcus dysenteriae and Salmonella typhi [9]. It inhibits the expressions of pro-in ammatory cytokines through NF-κB signaling pathway, which exhibited obvious inhibitory effect on LPS induced in ammation [10], and showd relatively high immunoregulatory activity and low cytotoxicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Filtrat yang masih mengandung berbagai jenis senyawa bioaktif akan memberikan respon penghambatan pertumbuhan yang berbeda-beda sehingga menyebabkan senyawa-senyawa bioaktif bekerja tidak sinergis (Miksusanti dan Marfinda., 2011). Selain itu, masuknya senyawa antibakteri tertentu akan dicegah oleh membran sel yang fungsinya sebagai penghalang (Fong et al, 2016). Membran luar bakteri gram negatif dapat berfungsi sebagai penghalang karena mengandung lipid tinggi dan permeabilitas tinggi dengan ketebalan membran >80 nm (Dwiyanti dkk., 2014).…”
Section: Pembahasanunclassified